Protocols for rat uterus isolation and decellularization: applications for uterus tissue engineering and 3D cell culturing - Padma, Arvind Manikantan; Tiemann, Tom Tristan (Decellularized scaffolds and organogenesis, 2017)
Sophisticated culturing conditions are required to grow cells in a three-dimensional (3D) environment. Cells then require a type of scaffold rich in proteins, growth factors, and signaling molecules that simulates their natural environment. Tissues from all species of animals have an organ-specific extracellular matrix (ECM) structure that plays a key role in cell proliferation and migration. Hence, the scaffold composition plays a significant role for any successful 3D cell culturing system. We developed a whole rat uterus ECM scaffold by the perfusion of detergents and ionic solutions through the vascular system of an isolated normal rat uterus in a process termed “decellularization.” The generated rat uterus scaffolds consist of a cell-free ECM structure similar to that of the normal rat uterus, and are thus excellent platforms on to which new cells can be added. Rat uterus 3D cell culturing systems based on these scaffolds could become valuable to decidual differentiation- and embryo implantation studies, or for investigating invasion mechanisms of endometrial cancer cells. They could also be used for the creation of tissue engineered uterine tissue, for partial or whole organogenesis developed for transplantation applications to treat absolute uterine infertility. This is a condition affecting about 1 in 500 women, and is only treatable by a uterus transplantation. This article provides valuable troubleshooting notes and describes in detail how to generate rat uterus scaffolds, including the delicate surgery required to isolate the uterus with an intact vascular tree which facilitates vascular perfusion and re-transplantation.